A commentary on 'generally representative is representative of none: pitfalls of IQ test standardization in multicultural settings' by A.B. Shuttleworth-Edwards. Issue 7 (2nd October 2016) - Sunderaraman, Preeti; Zahodne, Laura B.; Manly, Jennifer J.
Abstract: We offer an appraisal of Professor Shuttleworth-Edwards's commentary (2016) on the extraordinary challenges of assessment of cognitive function in a culturally, educationally, racially, and linguistically diverse population. First, we discuss the purpose of using intelligence tests in South Africa and beyond in order to clarify the reference group on which norms will be based. Next, we discuss the psychometric consequences of Pearson's decisions to not adapt their measure of intellectual functioning to the cultural background of the majority of South Africans, and to use a population-matched normative sample in which the disadvantaged group is in the majority. We echo Professor Shuttleworth-Edwards's call for large-scale empirical studies of cognitive test performance in a multicultural context. We conclude the article by urging the entire community of neuropsychologists to hold test companies accountable to strict, ethical, and comprehensive standards for production of accurate and appropriate measurement of cognitive function.